Propionato de testosterona promove neuroproteção em ratos idosos submetidos a um modelo progressivo de parkinsonismo - Souza, José Leandro Santos (2023)
Introduction: Senescence is one of the risk factors for the development of neurodegenerative diseases such as Alzheimer's, Parkinson's and Amyotrophic Lateral Sclerosis (ALS). Among them, Parkinson's disease (PD) is the second most frequent neurodegenerative disorder in the world, with the elderly population over 60 years of age being the most affected. PD has a higher prevalence in men than in women, highlighting sex hormones as a potential factor that contributes to the individual's susceptibility to this disease. With age, men experience a gradual decrease in testosterone levels, and this decrease is even more pronounced in patients with PD. Therefore, the objective of the present study was to evaluate the effects of previous and chronic administration of testosterone propionate (PT) against reserpine-induced monoaminergic deficits (RES) in elderly rats. Methods: Twenty-six male Wistar rats, aged between 18 and 24 months, were used. All experimental procedures were analyzed and previously approved by the UFS Animal Research Ethics Committee (CEPA/UFS) under protocol No. 37/2017. Animals were randomly divided into four groups (n = 6-7 per group): (1) CTRL, control group, treated with RES vehicle and testosterone propionate (PT), (2) RES, RES group, treated with reserpine, (3) RES+1PT group, treated with RES plus PT 1 mg/kg and (4) RES+5PT group, treated with RES plus 5 mg/kg PT. The animals received 30 previous injections of PT (1 or 5 mg/kg) intramuscularly daily. On the thirtieth day, the animals were submitted to the RES model, with 15 subcutaneous injections of RES (0.1 mg/kg) or vehicle administered for 30 days every 48 hours. Concomitantly with the start of the model induction, the animals continued to receive daily administrations of PT or its vehicle, totaling 60 administrations of PT and 15 administrations of RES. Throughout the experiment, the animals were submitted to behavioral tests of catalepsy, performed every 48 hours, oral movements (OM), performed after the effect of the 6th, 10th and 15th administration of RES and the open field test, performed on the last day of the experiment. 48 hours after the last RES injection, the animals were anesthetized and intracardiacly perfused. Results: It was observed that the PT was able to improve the body composition of the animals, avoiding the sudden weight loss caused by the model; we also observed that PT was able to attenuate the effects caused by RES in the MO, decreasing the amount of vacuum mastication and oral tremor, as well as being able to reduce the time of catalepsy. In this study we can also observe that PT was able to protect against the decrease in tyrosine hydroxylase labeling in the substantia nigra pars compacta (SNpc) and striatum. Conclusion: The results suggest that the previous and concomitant administration of PT promotes a neuroprotective effect on motor deficits and prevention of the reduction of the marker for tyrosine hydroxylase in the experimental model of parkinsonism induced by RES.